Energy efficiency of shape memory alloy - Yeo, Kai Yan. (2014)
This project is to investigate the energy efficiency of shape memory alloys (SMA) and the factors influencing the efficiency. In order to determine the energy efficiency, mechanical testing and thermal analysis are done to do so. The material used in this project will be the Nickel Titanium (NiTi) wires. The energy efficiency is calculated by determining the amount of work output by the NiTi wire divided by the amount of heat input into the NiTi wire. The method used in the project is joule heating where current and voltage is passed through the wire to generate heat so as to cause phase transformation.